After "it's over over there": Using record linkage to enable the reconstruction of World War I veterans' demography from soldiers' experiences to civilian populations. Issue 4 (2nd October 2018) - Cunningham, Angela R.
Abstract: In this article, I describe automatically linking newly accessible census data and World War I service records to enable a more holistic accounting of the connections between individual military experiences and emergent civilian population patterns. Employing models that can only be built from the individual level and examining relationships that are only traceable through linked data, I analyze how soldiers' wartime experiences may have inflected postwar marital outcomes and explore how linkage decisions shape results. In so doing, I show how quantitative methods can be used to question the adequacy of traditional WWI narratives, and provide an example of how, even with limited resources, the usefulness of historical microdatasets can be leveraged through record linkage.